Alternative psychopharmacologic treatments for pediatric catatonia: a retrospective analysis - Joshua R. Smith; Joshua R. Smith; Isaac Baldwin; Tasia York; Carina Anderson; Trey McGonigle; Simon Vandekar; Lee Wachtel; James Luccarelli; James Luccarelli (Frontiers in Child and Adolescent Psychiatry)
IntroductionPediatric catatonia is a highly co-morbid condition with treatment options often limited to electroconvulsive therapy (ECT) or lorazepam. However, lorazepam may not be readily available, and access to ECT is limited by restrictive legislation and stigma. This study aims to provide alternative treatment options for pediatric catatonia.MethodsThe study involved a single-site retrospective analysis of a private university hospital in the southern United States. The study included patients under eighteen with catatonia who received psychopharmacologic treatment with an agent other than lorazepam. The patients were evaluated with the Bush-Francis Catatonia Rating Scale (BFCRS), Kanner Catatonia Severity Scale (KCS), and Kanner Catatonia Examination (KCE) at the time of initial evaluation and upon stabilization. A retrospective clinical global impressions-improvement (CGI-I) score was assigned by four authors.Results102 pediatric patients diagnosed with catatonia were identified, and 31 met criteria for the study. 20 (65%) were white, 6 (19%) were Black, 4 (13%) were Hispanic, and 1 (3%) were Indian. Most patients (N = 18; 58%) were insured by Medicaid. The mean age at the time of catatonia diagnosis was 13.5 years. All patients were stabilized on either clonazepam or diazepam, with 21 (68%) requiring treatment with an additional medication of either an anti-epileptic, N-methyl-D-aspartate (NMDA) receptor antagonist, and aripiprazole or clozapine. Statistically significant reductions in the BFCRS [t = 11.2, df = 30, std = 6.3, p < 0.001, 95% CI = (7.8, 15.1)], KCS [t = 4.6, df = 38, p < 0.001, 95% CI = (12.0, 31.0)], and KCE [t = 7.8, df = 30, std = 1.8, p < 0.001, 95% CI = (1.9, 3.2)] were observed. For CGI-I the results showed that the estimated probability of observing a score better than no change (>4) is 0.976 [t.s. = 43.2, p < 0.001, 95% CI = (0.931,0.992)], indicating the average subject is expected to experience some improvement.DiscussionIn conclusion, all patients responded to these treatments with improvement in their catatonic symptoms. Alternative pharmacologic interventions for catatonia, including benzodiazepines other than lorazepam, valproic acid, NMDA receptor antagonists, and atypical antipsychotics were safe and effective in treating catatonia in this population.